Risk Factors for Subclinical Carotid Atherosclerosis among Current Smokers - Johnson, Heather M. (2010)
This study characterized the determinants of carotid atherosclerosis in a large, contemporary sample of current smokers. Associations between risk factors, carotid intima-media thickness (CIMT) and carotid plaque presence were determined by multivariable regression. Subjects included 1,504 current smokers (58% female) who were a median (interquartile range) of 44.7 (38–53) years old and smoked 25 (15–40) pack-years; 55% had plaque. Pack-years, age, male sex, non-white race, body-mass index, systolic blood pressure, small low-density lipoproteins (LDL), and total high-density lipoproteins were independently associated with CIMT (model R(2)=0.434, p<0.001). Pack-years (OR 1.14 per 10 pack-years, p=0.001), age (OR 1.75 per 10 years, p<0.001), body-mass index (OR 0.91 per 5 kg/m(2), p =0.035), and small LDL (OR 1.11 per 100 nmol/L, p<0.001), were independently associated with carotid plaque presence (model X(2)=210.7, p<0.001). The association between pack-years and carotid plaque was stronger in women (OR 1.09 per 10 pack-years, p(interaction)=0.018).